Guidelines for cellular and molecular pathology content in clinical trial protocols: the SPIRIT-Path extension. Issue 10 (October 2021) - Kendall, Timothy J; Robinson, Max; Brierley, Daniel J; Lim, Shujing Jane; O'Connor, Daniel J; Shaaban, Abeer M; Lewis, Ian; Chan, An-Wen; Harrison, David J; ,
Summary: The 2013 SPIRIT (Standard Protocol Items: Recommendations for Interventional Trials) Statement provides evidence-based recommendations for the minimum content to be included in a clinical trial protocol. Assessment of biospecimens is often required for trial eligibility or as part of an outcome evaluation, and precision molecular approaches are increasingly used in trial design. However, cellular and molecular pathology practices within trials have not been codified or formalised. We developed international consensus reporting guidelines for cellular and molecular pathology content in clinical trial protocols (the SPIRIT-Path extension) using an international Delphi process, which assesses candidate items generated from a previous systematic review, followed by an expert consensus meeting. 74 individuals from five continents responded, including clinicians, statisticians, laboratory scientists, patient advocates, funders, industry representatives, journal editors, and regulators. The SPIRIT-Path guidelines recommend 14 additional items (seven extensions to the SPIRIT checklist and seven elaborations) that should be addressed in trial protocols containing pathology content, alongside the SPIRIT 2013 Statement items. SPIRIT-Path recommends that protocols should document the individuals, processes, and standards for all cellular and molecular pathology components of the trial, including all stages of the specimen pathway and any digital pathology methods, with specific consideration of the value of trial data and biological tissues for additional translational studies.